Human Capital's Impact on Economic Growth In Wartime Conditions - Dligach, Andrii (Journal of Posthumanism, 2025)
State financing of human capital at the macro level is explored by analysing the dynamics of critical social budget expenditures from 2014 to 2023. The article investigates the essence of the concept of “human capital”, structures its components, and presents them in a multi-level analysis based on the principle of comparative aggregation. Sources of additional foreign funding and their volumes and dynamics since 2013 are also identified. The structure and problems of human capital at the micro level are examined, revealing dependencies between existing tasks and the factors that caused them. At the individual level of human capital, the qualities of personnel that hold significant value for employers are established. The Human Capital Index, Human Development Index, and Global Innovation Index are used to analyse the state of human capital in Ukraine and other countries. A regional analysis of wages, one of the key factors influencing the sufficiency and quality of human capital, is conducted, identifying regions with the highest and lowest wage levels and the balance of wages within each region.